Comparison studies on water quality and plankton production between perennial and non-perennial ponds in Bangladesh - Hossain, Md. Yeamin; Rahman, Mohammad Mustafizur; Jasmine, Saleha; Md Ibrahim, Abu Hanif; Ahmed, Zoarder Faruque; Ohtomi, Jun; El-Kady, Mohamed A H; Fulanda, Bernerd (Academic Journals, 2008)
The present study was conducted to compare the water quality and plankton availability between perennial and non-perennial ponds in Bangladesh for a period of six months during October 2004 to March 2005. All water quality parameters in perennial ponds were statistically different (p< 0.05) than that of non-perennial ponds except temperature. Free CO2, total alkalinity, pH and transparency were greater in the perennial ponds than that of non-perennial ponds, whereas an opposite result was observed in case of DO concentration. In general, water quality in the perennial ponds was more suitable for aquaculture than that of non-perennial ponds. Total phytoplankton and zooplankton availability were also greater in perennial ponds than that of non-perennial ponds. Absence or presence of aquatic macrophytes was the main cause of the water quality and plankton availability variation between perennial and non-perennial ponds. The present study suggests that non-perennial ponds will be suitable for aquaculture if aquatic macrophytes are removed.